2020
DOI: 10.1002/chem.202001372
|View full text |Cite
|
Sign up to set email alerts
|

Thermo‐Sensitive Dual‐Functional Nanospheres with Enhanced Lubrication and Drug Delivery for the Treatment of Osteoarthritis

Abstract: Osteoarthritis is a typical degenerative joint disease related to a lubrication deficiency of articular cartilage, which is characterized by increased friction at the joint surface and severe inflammation of the joint capsule. Consequently, therapies combining lubrication restoration and drug intervention are regarded as a promising strategy for the treatment of osteoarthritis. In the present study, thermo‐sensitive dual‐functional nanospheres, poly[N‐isopropylacrylamide‐2‐methacryloyloxyethyl phosphorylcholin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 40 publications
1
30
0
Order By: Relevance
“…In addition, in vitro experiments further showed that PNIPAM-PMPC nanospheres were biocompatible and protected chondrocytes from cytokine-induced degeneration. [ 157 ] HA/pNiPAM - Thermo-Sensitive; Slow release In vitro & vivo Human synovial fibroblasts; Mice Nanoparticles were biocompatible, providing a longer residence time at the injection site, protecting cartilage, reducing pro-inflammatory cytokines and maintaining callus thickness. [ 158 ] Chitosan oligosaccharide/ pluronic F127 KGN/Diclofenac sodium Thermo-Sensitive/Slow release In vitro & vivo Chondrocytes; Macrophage-like cells; BMSCs In order to achieve dual drug release, KGN was covalently cross-linked to the outer layer of the nanospheres, while DCF was loaded into the core of the nanospheres, showing the immediate release of DCF and the continuous release of KGN, which were independently controlled by temperature changes; The hypothermic nanospheres effectively inhibited the inflammation of chondrocytes and macrophage-like cells induced by endotoxin and induced mesenchymal stem cells to differentiate into cartilage.…”
Section: Different Drug-delivery Systems For Intra-articular Injectio...mentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, in vitro experiments further showed that PNIPAM-PMPC nanospheres were biocompatible and protected chondrocytes from cytokine-induced degeneration. [ 157 ] HA/pNiPAM - Thermo-Sensitive; Slow release In vitro & vivo Human synovial fibroblasts; Mice Nanoparticles were biocompatible, providing a longer residence time at the injection site, protecting cartilage, reducing pro-inflammatory cytokines and maintaining callus thickness. [ 158 ] Chitosan oligosaccharide/ pluronic F127 KGN/Diclofenac sodium Thermo-Sensitive/Slow release In vitro & vivo Chondrocytes; Macrophage-like cells; BMSCs In order to achieve dual drug release, KGN was covalently cross-linked to the outer layer of the nanospheres, while DCF was loaded into the core of the nanospheres, showing the immediate release of DCF and the continuous release of KGN, which were independently controlled by temperature changes; The hypothermic nanospheres effectively inhibited the inflammation of chondrocytes and macrophage-like cells induced by endotoxin and induced mesenchymal stem cells to differentiate into cartilage.…”
Section: Different Drug-delivery Systems For Intra-articular Injectio...mentioning
confidence: 99%
“…Microenvironmental-sensitive drug-release strategies have been attractive for PNP drug delivery. pH and temperature sensitive PNPs are rapidly evolving, including hollow dextran/poly (N-isopropyl acrylamide) NPs, 156 dual-functional poly[N-isopropylacrylamide-2-methacryloyloxyethyl phosphorylcholine] (PNIPAM-PMPC) nanospheres, 157 hyaluronic acid-poly(N-isopropylacrylamide) (HA-pNiPAM) nanospheres, 158 and chitosan oligosaccharide-conjugated pluronic F127 grafting carboxyl group nanospheres 159 which possess temperature-responsive release properties. Previous studies showed that NH 4 HCO 3 laden poly (lactic-co-glycolic acid) (PLGA) NPs demonstrate pH-responsive drug release.…”
Section: Different Drug-delivery Systems For Intra-articular Injectio...mentioning
confidence: 99%
“…Through surface modification, the hydrogel microspheres could play a bearing lubrication role in the joint cavity. Zhang et al [26] loaded the drug within hydrogel microspheres, which both prematurely prevented the drug from being removed and controlled its release. The appropriate size of hydrogel microspheres enables them to avoid being cleared by the blood or lymphatic vessels to the greatest extent, resulting in a prolonged half-life.…”
Section: Introductionmentioning
confidence: 99%
“…To overcome these limitations, the development of drug delivery systems has been considered crucial to modulate the desired cell phenomenon adjusted to the intended use. Among available systems, halloysite clay nanotubes (HNTs) have been proven to be an adequate platform to promote sustained drug delivery in association with GelMA. , HNTs are naturally formed by the exfoliation process of aluminosilicate minerals (Al 2 Si 2 O 5 (OH) 4 · n H 2 O). This process results in a bilayered hollow tubular structure with a positively charged inner surface afforded by alumina composition (Al–OH) and a negatively charged external surface consisting of silicon dioxide (SiO 2 ).…”
Section: Introductionmentioning
confidence: 99%